Association Between Mental Health Outcomes and Changes in Lifestyle Behavior Index Among Saudi Adults 16 Weeks After COVID-19 Pandemic Lockdown Release - Abd El-Fatah, Nesrin Kamal; Alshehri, Abdalsalam Abdullah; Alsulami, Fatma H.; Alasmari, Norah; Osman, Nermin A. (Frontiers in Public Health, 2022)
Background The current (coronavirus disease 2019 [COVID-19]) pandemic is still uncontrolled with associated dramatic changes in daily lifestyle activities. Evidence for studying the impact of these health behavior changes on our mental health is limited. Therefore, this study aimed to estimate the prevalence of psychological distresses and assess their influence by the change in the composite lifestyle behaviors before the COVID-19 pandemic till 16 weeks after the lockdown release in Saudi Arabia. Methods This cross-sectional study was conducted between October 10 and 31, 2020 by posting an online survey on social media platforms (WhatsApp and Twitter) to collect data on participants' sociodemographic, lifestyle behaviors, and mental health aspects using a validated Arabic version of the short-form version of the Depression Anxiety Stress Scales-21 (DASS-21). Results A total of 363 responded to the questionnaire. The mean age was 36.26 ± 8.54 years, and 238 (65.6%) were men. Depression, stress, and anxiety were reported in 37.5, 26.7, and 16.5% of the participants, respectively. Negative lifestyle behavioral changes were significantly associated with stress and anxiety (p < 0.05). Logistic regression revealed that financial distress and history of psychiatric illnesses were common significant factors for developing the psychological distresses. Conclusion Throughout the post-lockdown stage of the COVID-19 outbreak in Saudi Arabia, there was an evidence of psychological distresses among the adults. Negative health-related changes are directly linked with increased psychological distress. Effective health promotion strategies directed toward adopting and maintaining positive change in the composite health behaviors are crucial.